Development of Ubiquitous Learning Environment Based on Moodle Learning Management System - Suartama, I Kadek; Setyosari, Punaji; Sulthoni, Sulthoni; Ulfa, Saida (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The digitalization of society, changes in the structure of education, and increasingly rapid resources have accelerated the development of an open learning environment. The application of electronic learning and mobile learning raises several new problems such as alienating students from the real world, the difficulty of students focusing on learning goals, giving students opportunities to spend their learning time with entertainment, to the problem of increasing the cognitive load of students. Ubiquitous learning, as a continuation of the evolution of electronic learning and mobile learning, offers more than just the latest educational ideas or methods, where this system can accommodate students and their learning styles by providing adequate information anytime and anywhere based on their characteristics, needs, and desire to improve academic performance and productivity. The purpose of this study is to 1) develop the ubiquitous learning environment including the ubiquitous learning portal built with the Moodle LMS, and the ubiquitous learning course in the Instructional Media course 2) find out the feasibility of the ubiquitous learning environment that has been developed. This study used the R&D for Education model implementing some stages including analysis, design, development, and evaluation. All stages have been completed to make a portal and ubiquitous learning course in the Instructional Media course that meet the eligibility criteria as a source/instructional media and has feasibility to use in learning.